KEPUASAN PELANGGAN NETFLIX DI KOTA MEDAN DIUKUR DENGAN NILAI PELANGGAN, BRAND EXPERIENCE DAN USER EXPERIENCE - Tarigan, Miska Irani Br; Siahaan, Renni Novia (Jurnal Riset Akuntansi & Keuangan, 2023)
Netflix is a digital streaming service provider that offers digital content to its subscribers in the form of television shows, series, films, anime, documentaries, and exclusive content that can be viewed at any time and from any location. The purpose of this research is to determine the impact of customer value, brand experience, and user experience on customer satisfaction with Netflix Digital Streaming Services in Medan City. This study is an associative study, and the data used is quantitative data. This study's population consists of Netflix subscribers in Medan Sunggal District, Medan City. This study included 200 people as samples. Customer Value has a positive and significant effect on customer satisfaction for Netflix subscribers in Medan City, according to the findings of this study, with a regression coefficient of 0.212 and a significance value of 0.028. With a regression coefficient of 0.324 and a significance value of 0.020, Brand Experience has a positive and significant effect on customer satisfaction for Netflix subscribers in Medan City, and User Experience has a positive and significant effect on customer satisfaction for Netflix digital streaming services in Medan City, with a regression coefficient of 0.304 and a significance value of 0.022. Meanwhile, customer satisfaction for the Netflix digital streaming service in Medan City is positively and significantly influenced by Customer Value, Brand Experience, and User Experience.